“Should Women Smile at Mona Lisa Smile (2003)?” A Feminist Critical Discourse Analysis of Gender Representation - Solong, Alicia Ferani; Petrus Jacob Pattiasina (The Journal of Society and Media, 2025)
This article applies Feminist Critical Discourse Analysis (FCDA) to Mona Lisa Smile (2003) to examine how nostalgic Hollywood cinema both reinscribes and subverts 1950s gender norms. Five strategically selected scenes (comprising 23 dialogue turns and accompanying visuals) were analysed using Lazar’s (2007) three-stage FCDA, supported by Eckert and McConnell-Ginet’s (2013) linguistic frameworks. The analysis reveals a sustained ambivalence, where feminist language is frequently undermined by visual and narrative conventions that re-centre domestic ideals. Drawing on Butler’s theory of performativity, Bourdieu’s concept of symbolic power, and audience reception studies (Radner 2021; Negra 2009), the study situates the film within broader patterns of postfeminist media. Comparative references to other "teacher films" and retro-set narratives illuminate how Mona Lisa Smile aligns with, yet diverges from, genre conventions in its ideological messaging. Findings suggest that patriarchal ideologies persist by assimilating the rhetoric of emancipation, highlighting the importance of teaching such films as contested texts. Implications for gender-sensitive media pedagogy and critical film literacy are discussed.